(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The study was undertaken to ascertain the constraints and strategies towards improving cassava production and processing in Enugu north agricultural zone of Enugu State, Nigeria. Data were collected from 60 cassava producers and processors (farmers) through the use of structured interview schedule. Multistage sampling technique was applied in the selection of respondents. Mean, standard deviation and exploratory factor analysis were used in realizing the objectives. The results showed that the major constraints to cassava production and processing were agronomic factors, technical/institutional factors and financial factors. The major strategies for improving cassava production and processing include making planting material available at the right time in the right places and at reduced prices, establishment of starch based industries in rural areas for processing cassava and formation of farmers’ cooperative societies to enhance farmers’ access to information and production facilities. The study, therefore, recommended that starch based industries should be established in rural areas for cassava processing in order to encourage both producers and processors for added value. This will also encourage youth in agriculture for economic growth. Keywords: Cassava production and processing; constraints and strategies; Nigeria. DOI: 10.3329/bjar.v35i3.6445 Bangladesh J. Agril. Res. 35(3) : 387-394